AEGLE MARMELOS A POTENTIAL MEDICINAL TREE: AN OVERVIEW - Sanghi, Shail Bala; Mushtaq, Sabira (International Journal of Research -GRANTHAALAYAH, 2017)
Aegle marmelos family rutaceae is an alleged ayurvedic medicinal tree commonly known as the bael. It is medium sized tree growing throughout the forest of India of altitude 1200 meter. It is found all over India, from sub-Himalayan forest, Bengal, central and south India. It is considered to be a holy tree in India. Various parts of this plant such as leaves, roots, seed, bark and fruit, possess anti-microfilarial, antifungal, immunomodulatory, anti-proliferative, wound healing, antifungal, analgesic, anti-inflammatory, antipyretic, hypoglycaemic, antidyslipidemic, anti-fertility, and insecticidal activity. Various phytopharmacological evaluations have been reported in this writing for the important potential of the Aegle marmelos.